UNGKAPAN IDIOMATIK BAHASA INGGRIS DAN PERMASALAHAN PENERJEMAHANNYA KE DALAM BAHASA INDONESIA - Yuwono, Suhud Eko (MAGISTRA, 2004)
Generally speaking idioms are fixed expressions which belong to language specific phenomena. There is usually no equivalence for idiom translation. This may improse problems in translating idiomatic expression from  one language to another, particularly because certain idioms are not easily recognizable. The following discussion reviews some formal and meaning aspects of English idiom and the need of contextual descriptions to the understand them, in order to obtain its nearest translation equivalence in Indonesia.